ПЕРЕДАЧА НАГРУЗКИ ОТ ДВУХ ОДИНАКОВЫХ КОЛЬЦЕОБРАЗНЫХ СТРИНГЕРОВ К БЕСКОНЕЧНОЙ ПЛАСТИНЕ С УЧЕТОМ ПОЛЗУЧЕСТИ - Р. С. Туманян (National Academy of Sciences of Armenia)
A contast sum is observed by creep theories order, on transfer from the similar ring cover plate to an elastic infinite one. A sum is reduced to Volter’s operator containing singular integral-differential equation’s solution by time. By means of chebishev’s orthogonal multiple-member system an equation was brohght to Volter’s linear integral equation’s infinite system on second degree. The investigation of mentioned system was done by principle of pressured reflections. Particular cases were observed.
Keywords: Generalities, axiomatics, foundations of continuum mechanics of solids; Thin bodies, structures; Mechanics of deformable solids